Recurrent ATP2A2 p.(Pro602Leu) mutation differentiates Acrokeratosis verruciformis of Hopf from the allelic condition Darier disease. Issue 7 (12th May 2017) - Ronan, Anne; Ingrey, Angela; Murray, Natalia; Chee, Paul
Abstract : Darier disease and Acrokeratosis Verruciformis of Hopf (AKV) are rare disorders of keratinization with autosomal dominant inheritance and very distinct clinical pictures. Both have been shown to be caused by mutations in ATP2A2 (ATPase, Ca ++ transporting, cardiac muscle, slow‐twitch) a gene encoding one of the SERCA (sarcoplasmic/endoplasmic reticulum calcium ATPase2) intracellular pumps with a crucial role in cell‐to‐cell adhesion in both skin and heart. While hundreds of different missense and nonsense mutations cause Darier disease, only one missense mutation, p.(Pro602Leu), has been identified in families with AKV. We report a family with AKV due to the p.(Pro602Leu) mutation and discuss implications for this recurrent mutation on knowledge of ATP2A2 structure and function.